1998
DOI: 10.1258/002367798780599893
|View full text |Cite
|
Sign up to set email alerts
|

The influence of transportation stress on selected nutritional parameters to establish the necessary minimum period for adaptation in rat feeding studies

Abstract: The optimal length of the adaptation period after transportation of rats, to be used in nutritional studies, was investigated in this study. After intracontinental transportation of rats by car and by air to and from the laboratory for a total period of 15 h, measurements were carried out for a period of 3 weeks after transport. Control and transported animals were housed in the same laboratory before and after transportation. During transport the animals had access to food and water. As blood collection could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 5 publications
5
35
0
1
Order By: Relevance
“…The results disagree with the findings of Liste et al (2009), who did not measure EOF, but showed that 8-h lairage was enough for rabbits to recover from stress due to 3-h transportation by road. Similarly, studies in rats and in rabbits have recommended adaptation periods of 3 days and 48 h, respectively, yet periods of 3-5 days after transportation have been recommended for rats used in toxicology studies (Damon et al 1986;Toth & January 1990;van Ruiven et al 1998). The variations in the results may be due to differences in transportation conditions, breed of rabbit, season and variables measured.…”
Section: Post-transportation Periodmentioning
confidence: 99%
“…The results disagree with the findings of Liste et al (2009), who did not measure EOF, but showed that 8-h lairage was enough for rabbits to recover from stress due to 3-h transportation by road. Similarly, studies in rats and in rabbits have recommended adaptation periods of 3 days and 48 h, respectively, yet periods of 3-5 days after transportation have been recommended for rats used in toxicology studies (Damon et al 1986;Toth & January 1990;van Ruiven et al 1998). The variations in the results may be due to differences in transportation conditions, breed of rabbit, season and variables measured.…”
Section: Post-transportation Periodmentioning
confidence: 99%
“…many studies have reported that stress induced by transportation significantly increased the corticosterone concentration in various species of animals including mice, dogs, pigs, and cattle [1,11,20,23]. however, some researches have reported that the blood corticosterone concentration was significantly lowered in transport animals 1 day after transportation [21]. Therefore, we investigated how the stress induced by air transportation affected the corticosterone concentration.…”
Section: Discussionmentioning
confidence: 97%
“…An increase in GRP78 is known to occur in response to stressful conditions that disrupt the function of the endoplasmic reticulum (ER) [3,14]. In addition, it was demonstrated that animals in flight showed a higher concentration of corticosterone (cortisol or adrenal steroid hormone) than controls [10], which was significantly lower in the transported animals 1 day after transport [21]. Thus, stress proteins (HSP70, GRP78) and corticosterone are useful biomarkers of many environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Συγκεκριμέ να, για τα ζώα εργαστηρίου έχει μελετηθεί η επίδραση του stress στα επίπεδα γλυκόζης στο πλάσμα, όπου πα ρατηρήθηκε σημαντική αΰξησή της σε μΰες (Aguila et al 1988, Tabata et al 1998. Επιπλέον, έχει μελετηθεί η επίδραση του stress της μεταφοράς στο Σ.Β., στην κατανάλωση τροφής και νεροΰ, στη συμπεριφορά και ψυχική υγεία, καθώς και στη μεταβολή βιοχημικών πα ραμέτρων στο αίμα επιμΰων (van Ruiven et al 1998). Κατά συνέπεια, πρέπει να καταβάλλεται κάθε δυνατή προσπάθεια μείωσης του stress της μεταφοράς.…”
Section: β) παραλαβηunclassified